Factors influencing adoption of self-monitoring of blood pressure among hypertensive patients in primary healthcare in Vietnam: a cross-sectional facility-based study - Nguyen Hoang Giang; Nguyen Thi Phuong Lan; Le Thi Kim Anh; Dominika Plancikova; Viera Rusnakova; Nguyen Thi Thang; Jaap A.R. Koot (BMC Primary Care)
Abstract Background Hypertension is an increasing health problem in low- and middle-income countries such as Vietnam. Self-monitoring of blood pressure (SMBP) is a crucial component of hypertension management in primary healthcare (PHC) and stimulated by healthcare providers. Yet, its adoption remains suboptimal. This study examines the application and contributing factors to adoption of SMBP among hypertensive patients in a PHC setting in Vietnam. Methods A cross-sectional study was conducted among 989 hypertensive patients managed at commune health stations (CHSs), part of PHC, in two provinces in Vietnam. Participants were selected using systematic random sampling from CHS patient lists. Data were collected through structured interviews and analysed using descriptive statistics and multivariate logistic regression to identify factors contributing to SMBP practices. Results The prevalence of SMBP among hypertensive patients was 43.1%. Among those who practiced SMBP, 42.3% monitored their blood pressure daily, while 57.7% measured it at least weekly. The majority (80.2%) used home sphygmomanometers, 12% relied on friends or relatives with BP monitoring devices, 7.8% went to a pharmacy of health worker’s home to measure BP. Multivariate analysis identified key factors associated with SMBP adoption. Higher educated persons were more engaged in SMBP (p < 0.001). Pensioners were more likely to engage in SMBP than unemployed individuals (OR = 2.2; p < 0.001). Higher knowledge of hypertension management (OR = 1.10; p < 0.001) and regular physical activity (OR = 1.54; p = 0.005) were also positively associated with SMBP practice. Persons living in Ninh Bing were also more likely to apply SMBP (OR = 1.58; p < 0.001). Conclusion Less than half of hypertensive patients practiced SMBP, highlighting a need for targeted interventions to promote self-monitoring. Key facilitators for patients include better health knowledge, socioeconomic stability, and local healthcare service availability. On the service provision side, strategies to improve SMBP adoption should focus on increasing patient education, ensuring the affordability of BP monitoring devices, and strengthening the role of primary healthcare providers in coaching patients on SMBP. A patient-centred, community-based approach is necessary to enhance hypertension self-management and improve overall cardiovascular health outcomes in Vietnam.